What makes you a 'hero' for nature? Socio-psychological profiling of leaders committed to nature and biodiversity protection across seven EU countries. Issue 5 (12th May 2018) - Scopelliti, Massimiliano; Molinario, Erica; Bonaiuto, Flavia; Bonnes, Mirilia; Cicero, Lavinia; De Dominicis, Stefano; Fornara, Ferdinando; Admiraal, Jeroen; Beringer, Almut; Dedeurwaerdere, Tom; de Groot, Wouter; Hiedanpää, Juha; et al.
Abstract : Biodiversity loss is a widely debated world problem, with huge economic, social, and environmentally negative consequences. Despite the relevance of this issue, the psychological determinants of committed action towards nature and biodiversity have rarely been investigated. This study aims at identifying a comprehensive social-psychological profile of activists committed to biodiversity protection and at understanding what determinants best predict their activism. A questionnaire investigating relevant social-psychological constructs identified in the literature on environmental activism was administered to 183 outstanding leaders (vs. non-leaders) in biodiversity protection across seven EU countries. Leaders (vs. non-leaders) in biodiversity protection showed, among other constructs, higher scores on environmental values, attitudes, identity, perceived control, a feeling of union and spirituality with nature, and willingness to sacrifice for their cause. Results are discussed within the theoretical framework of a motivation model of committed action for nature and biodiversity protection. Applications of the results are also proposed.